Enhanced antifouling and flux performances of a composite membrane via incorporating TiO2 functionalized with hydrophilic groups of L‐cysteine for nanofiltration. (25th January 2022) - Gholami, Foad; Zinatizadeh, Ali Akbar; Zinadini, Sirus; Rittmann, Bruce E.; Torres, Cesar I.
Abstract: A new TiO2 nanoparticle modified via L‐cysteine is presented in this study. The L‐cysteine (cys) modified TiO2 nanomaterials impact as membrane modifier was examined in terms of pure water flux, hydrophilicity, morphology, and resistance ability. The mixed matrix membranes morphology investigated by using scanning electron microscope (SEM), atomic force microscopy (AFM), water contact angle measurement, porosity and pore size and Fourier transform infrared spectroscopy analysis. Membrane hydrophilicity and permeation flux were notably improved by introducing TiO2 ‐cys nanomaterials to the membrane matrix. The SEM image indicated the expanded finger‐like pores for the modified membranes comparing to the bare polyethersulfone (PES). The obtained AFM image exhibited lower surface roughness parameters for the modified membranes. In case of prepared membranes assessment, dye removal capability using the direct red‐16 and real liquorice wastewater were examined. The results confirmed that the modified membranes indicated high‐ranking dye rejection ability (more than 98% for direct red‐16 and 90% for real liquorice wastewater) comparing to the bare membrane (86 ± 2.58%). The antifouling tests were run based on milk powder (1000 mg/L) filtration and the best antifouling performance was obtained for 0.5 wt% of TiO2 ‐cys membrane (flux recovery ratio = 90.57 ± 2.71%, R ir  = 9.43 ± 0.28%). Also, the results showed high potential of TiO2 ‐cys nanomaterials for membrane hydrophilicity enhancement.